Varicella Zoster Virus Pneumonitis and Brainstem Encephalitis Without Skin Rash in an Immunocompetent Adult. (6th August 2014) - Nandhagopal, Ramachandiran; Khmeleva, Nelly; Jayakrishnan, B.; White, Teresa; Al Azri, Faisal; George, Jojy; Heintzman, Anna; Al Zeedy, Khalfan; Rorke-Adams, Lucy; Gujjar, Arunodaya R.; Schmid, D. Scott; Al-Asmi, Abdullah; et al.
Abstract: Varicella zoster virus (VZV) pneumonitis and brainstem encephalitis developed in an immunocompetent adult without rash. Chest computed tomography exhibited nodularity; lung biopsy revealed multinucleated giant cells, Cowdry A inclusions, VZV antigen, and DNA. Varicella zoster virus central nervous system disease was verified by cerebrospinal fluid (CSF) anti-VZV IgG antibody with reduced serum/CSF ratios.